Impact of organizational trust on organizational commitment: the moderating effect of national identity - Abdullah M. Alomran; Tarek Sayed Abdelazim Ahmed; Ayman Mounir Kassem (Cogent Social Sciences)
The main objective of this study is to examine the moderating effect of employees’ national identity on organizational trust and organizational commitment among employees in hotel establishments in the Hail region, of Saudi Arabia. A conceptual model was developed to find a mechanism through which organizational trust impacts organizational commitment dimensions through the factor of national identity. Multiple statistical analyses were applied to test the hypotheses developed in this study using structured equation modelling. These hypotheses were tested through a survey questionnaire. Measurements of organizational trust and organizational commitment were developed. 212 employees from 20 hotels in Hail, Saudi Arabia, voluntarily participated in the current study. Their responses were examined using linear regression, confirmatory factor analysis and structural equation modelling. The findings reveal that organizational trust is a positive predictor of all types of organizational commitment (affective, continuance, and normative). The results also indicate that nationality does not significantly moderate the impact of organizational trust on either affective commitment or normative commitment. However, it significantly moderates the relationship between organizational trust and continuance commitment. This study may assist managers in better understanding the importance of organizational trust and organizational commitment. Cultivating a trusting environment can help increase employees’ trust in their establishments, which can lead to better levels of organizational commitment and improved job performance, which can be reflected positively in their profitability. The study highlights that hotel establishments should emphasize organizational-trust-related dimensions, including competence, dependability, integrity, and transparency, as they can lead to the organizational commitment of employees and their intention to continue with their establishments.